EVALUATION OF CHILD HEALTH IN TRANSBAIKAL REGION - N. I. Zyubina; G. I. Bisharova (Acta Biomedica Scientifica)
The paper presents the results of health status study in pediatric population of the Transbaikal region. It was shown the prevalence of some forms of chronic diseases in dependence on age and residence. In addition, we revealed factors influencing to pathology development.